Avaliação do nível de expressão de MAGE A1 e BORIS e do perfil de metilação em carcinoma de células escamosas bucal - Claudia Maria Pereira (2011)
Despite the advances in the treatment management of Oral squamous Cell Carcinoma (OSCC) there has not been a significant improvement in the 5 years survival rate, of which is about 50%, in the last decades. In the light of these data the search towards novel therapies for OSCC has become necessary. Cancer Testis Antigens (CTAs) are antigens whose expression is limited to germ cells and to several types of cancer. Due to their immunogenic potential, the CTAs are considered promising targets molecules for cancer vaccines development. Immunotherapeutic approaches have gained interest in the head and neck squamous cell carcinoma treatment. The aim of this project is to evaluate MAGE A1 and BORIS expression in OSCC samples and to investigate the association of hypomethylation with this event. The expression levels of MAGE A1 and BORIS were investigated by real time PCR in 15 primary OSCC patient samples compared to 10 normal samples. Our data show that these genes were absent and/or underexpressed in normal and tumor evaluated samples. Subsequently the gene expression was evaluated through conventional PCR in 20 primary OSCC samples and 10 normal mucosal samples. Similar to the real time PCR results, these genes were absent and/or underexpressed in all of the evaluated samples. Post Sodium bisulfite sequencing analysis showed a hypomethylation level present on the CpG island of MAGE A1 (~23%) in CCEB samples similar to those found on normal mucosal samples. In the mmunohistochemical evaluation was detected the presence of MAGE A1 protein in 80% of OSCC samples, but not in normal mucosal samples. BORIS protein was detected in 100% of OSCC and normal mucosal samples. Although MAGE A1 and BORIS transcripts have not been detected in any OSCC samples, the proteins of these genes have been detected in these samples. The presence of splice variants of MAGE A1 and BORIS are capable of explaining this finding.